The role and behaviour of Chinese agricultural enterprises in sub-Saharan Africa : case studies of Mozambique and the Democratic Republic of Congo - Asanzi Mbeyata, Philippe (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.